Neuroplastin 65 deficiency leads to the impairment of visual function through affecting ribbon synapse in retina of mice - Zeng, Jiu-jiang; Chen, Ling; Liu, Li-fen; Wang, Jia-lu; Cheng, Jie; Zheng, Ya-ni; Zhang, Lei; Zhang, Xiao-ming; Yuan, Qiong-lan (Frontiers in Cellular Neuroscience, 2025)
Neuroplastin 65 (NP65) is a synapse-enriched glycoprotein in the central nervous system and is implicated in synaptic plasticity. In the present study, we found that NP65 knockout (NP65 KO) mice exhibit impaired visual function, including reductions in the amplitude of b-wave in scotopic flash electroretinogram (fERG), the amplitude of N1 and P1 waves in flash visual evoked potentials (fVEP), and the constriction rate in pupillary light reflexes (PLR). In wild-type (WT) mice, NP65 is specifically enriched in the synaptic ribbon (SR) of ribbon synapses labeled by Ribeye in the retina. We found that NP65 KO mice display nearly normal architecture of the retina. However, NP65 KO mice show a significant decrease in the immunoreactivity of presynaptic postsynaptic density protein 95 (PSD95), synaptophysin (SYN) and Ribeye in the outer plexiform layer (OPL). Moreover, the electron microscopy displays a decrease in synaptic ribbons and defects in postsynaptic structures in the ribbon synapses of the OPL in NP65 KO mice. In addition, we found that the apposition of presynaptic photoreceptor axonal terminals and postsynaptic bipolar cell dendrites in the OPL is misplaced in NP65 KO mice. Finally, we show that intravitreous injection of AAV-NP65 reverses the visual dysfunction, increases Ribeye expression and restores the normal arrangement in the OPL of NP65 KO mice. Together, our findings reveal that NP65 deficiency leads to visual function impairment by affecting ribbon synapses in the OPL of mice, suggesting that NP65 is critical for visual function in mammals and a potential target for degenerative retinopathy.